HUBUNGAN PENGUASAAN STRUKTUR KALIMAT DAN MINAT MENULIS DENGAN KEMAMPUAN MENULIS EKSPOSISI PADA SISWA KELAS VIII SMPN 14 BANDAR LAMPUNG - Khanif, Abdul (Lentera: Jurnal Ilmiah Kependidikan, 2021)
This study aims to describe the correlation between sentence structure mastery and writing interest with the exposition writing ability in class VIII SMPN 14 Bandar Lampung in the 2020/2021 academic year. This research is due to the fact in the field that the ability to write exposition, mastery of sentence structure and interest in writing needs to be developed. The method used in this research is a questionnaire and a test. Testing the research hypothesis using the correlation coefficient test, product moment and multiple correlation. Previously, the analysis requirements test was carried out, namely the normality and linearity test of the data. The results showed that: (1) There is a positive and significant correlation between mastery of sentence structure and the ability to write exposition as indicated by the correlation coefficient of 0.312 and the coefficient of determination is (r2) = 0.596 or 59.60%. (2) There is a positive and significant correlation between writing interest and the ability to write exposition as indicated by the correlation coefficient of 0.312 and the coefficient of determination (r2) = 0.508. or by 50.80%. (3) There is a significant correlation between mastery of sentence structure and writing interest with the ability to write exposition as indicated by the correlation coefficient of 4.153 and the coefficient of determination is (r2) = 0.656. or 65.60%.